Inhibitory effects of midostaurin and avapritinib on myeloid progenitors derived from patients with KIT D816V positive advanced systemic mastocytosis - Lübke, Johannes; Naumann, Nicole; Kluger, Sebastian; Schwaab, Juliana; Metzgeroth, Georgia; Hofmann, Wolf-Karsten; Fabarius, Alice; Reiter, Andreas; Jawhar, Mohamad (Leukemia, 2019)
Advanced systemic mastocytosis (advSM) is characterized by the presence of an acquired KIT D816V mutation in >90% of patients. In the majority of patients, KIT D816V is not only detected in mast cells but also in other hematopoietic lineages. We sought to investigate the effects of the KIT-inhibitors midostaurin and avapritinib on single-cell-derived myeloid progenitor cells using granulocyte-macrophage colony-forming-units of patients with KIT D816V positive advSM. Colonies obtained prior to treatment were incubated in vitro with midostaurin (n = 10) or avapritinib (n = 11) and showed a marked reduction (≥50%) of KIT D816V positive colonies in 3/10 (30%) and 7/11 (64%) patient samples, respectively. Three of those 7 (43%) avapritinib responders were resistant to midostaurin in both, in vitro and in vivo. Colonies from four patients with high-risk molecular profile and aggressive clinical course were resistant to both drugs. The in vitro activity of midostaurin strongly correlated with clinical and molecular responses, e.g., relative reduction of KIT D816V allele burden and the proportion of KIT D816V positive colonies obtained after six months midostaurin-treatment in vivo. We conclude that the colony inhibition assay provides useful information for prediction of responses on midostaurin and that avapritinib has a superior in vitro activity compared to midostaurin.
Gesehen am 04.07.2019